LA EDUCACIÓN SUPERIOR Y EL PROCESO DE TRANSFORMACIÓN SOCIAL EN EL ECUADOR - Borja Herrera, Laura Amarilis (2014)
The present investigation was carried out from birth as an Independent Republic Ecuador; and the analysis on the course of the Ecuadorian higher education, beginning with the promulgation of the First Consti-tution of September 23, 1830, until his last force since September 28, 2008, representing a total of twenty, which they have provided the basis for this study.With this, the information has been synthesized in six phases, they have not been determined with a speci-fic range of time, but based on the expectation that generated the constitutional framework that allowed to move from one state to another, identifying each of them, the time of analysis, the most outstanding actions that allow us to understand and historically relate the process of transformation of the Ecuadorian higher education that is living in the moment, where all institutions of the system are subject to improvement plans or strengthening, as part of the national policy of Good Living and social transformation proclaimed in the new Constitution in force. With this information, you will reach the respective conclusions.